CONTENT MARKERS OF ABILITY TO PROJECT SELF-REALIZATION OF THE FUTURE TEACHER OF HIGHER EDUCATION - Cопін, О. І. (SWorldJournal, 2022)
The article highlights the state of studying the problem of the ability to project self-realization of the future teacher of higher education. Considers the specifics of this concept in the process of professional training of a high school teacher and car